Sagittarius-A and the Philosophical Black Hole: What Lies at the Center? - Tekin, Ömer Fatih (Turkish Academic Research Review, 2025)
Whether considered from a theological perspective or through the lens of classical physics, human beings have historically been placed at the center of the universe. Other living beings are deemed significant insofar as they contribute to the survival of humanity. If they fail to benefit humans or pose a threat, they are either removed from human proximity or stripped of their right to life. This anthropocentric view has also been rationalized philosophically, with the God-Mind-Man triad evolving into a narrative that still persists. Similarly, in monotheistic religions, God, having imparted a portion of His essence to humanity, created humans as the most significant beings, offering them dominion over all the earth’s resources. This has symbolically placed humanity on a solid, immovable foundation—the Earth—designated as the center. However, despite this perceived dominion, humans remain vulnerable and insignificant in the face of natural phenomena such as earthquakes, floods, and storms, commonly called disasters. These occurrences starkly reveal humanity's frailty. Consequently, while humans are considered central and everything else is seen as existing for their sake, in the face of immense forces, they become powerless, displaced from the center, and reduced to a state no different—or perhaps even less significant—than other beings. This backdrop sets the stage for a paradigm shift in the contemporary era, where scientific advancements have shown that human centrality is an increasingly untenable construct. Humans are no longer the dominant, central entities but instead comparable to an insignificant celestial body orbiting in the void. This realization was epitomized by the photograph of Sagittarius-A, the supermassive black hole at the center of the Milky Way galaxy. Confronted with this reality, humanity has lost its privileged position and now occupies the same rank as any ordinary being—or even an inanimate object. Once accepted as universal truths, history's dominant narratives have been overturned. The depiction of humans as a superior, central existence is now reimagined as akin to a purposeless entity drifting in the void. This revaluation, catalysed by the visual evidence of Sagittarius-A, underscores the profound implications of this astronomical discovery. This article explores the philosophical significance of Sagittarius-A, a supermassive black hole at the heart of the Milky Way, and its connections with contemporary philosophical thought. Black holes, while crucial phenomena in modern physics and astronomy, also provoke profound philosophical inquiries. Sagittarius-A, as a central cosmic entity, Sagittarius-A raises metaphysical and ontological questions about the universe's structure, the nature of time, and our understanding of existence. The article argues that black holes serve not only as astronomical objects but also as philosophical tools that challenge human cognition and our attempts to comprehend the ultimate nature of the universe. It examines the physical characteristics of black holes, particularly their effects on space and time within the framework of general relativity and considers their implications for philosophical thought. Discussions include the philosophical perspectives on the warping of time and space by black holes, the relationship between human consciousness's limitations, and the infinite structure of the universe. Moreover, the article delves into the metaphysical impact of black holes, focusing on their internal structure and event horizons and how these challenge the boundaries of human consciousness and understanding. The relationship between black holes and concepts such as being, nothingness, and information loss is analysed, highlighting how these phenomena influence the relativity of meaning. In conclusion, this study underscores how black holes, particularly Sagittarius-A, function as scientific and philosophical objects, provoking intellectual awakening and posing new questions for humanity. It further suggests that humanity may exist in a metaphorical philosophical black hole in the current era.